Safe Performance in a World of Global Networks Case Studies, Collaborative Practices and Governance Principles - Le Coze, Jean-Christophe; Journé, Benoît (SpringerBriefs in Applied Sciences and Technology; SpringerBriefs in Safety Management, 2024)
This open access book provides an analytical and critical outlook, by leading scholars, of the impact of various trends in the quality of collaboration and resulting safety outcomes that arise from the evolution of traditional integrated production within a single firm into a complex web of partnerships and supply chains. In the face of increasing fragmentation within industrial production and the associated rise in the complexity of inter-organizational communication and transaction,this book analyses causal factors such as cost pressures, globalization of demand, increasingly flexible resource allocation and work organization, changes in legal liability and the possibilities afforded by information technology. Various case studies focus on the effects of crossing boundaries between organizations, between different trades and professions and between countries, assessing the effect of variations in regulatory structures and national cultures. Furthermore, they illustrate the wide range of organizational forms to be found in high-hazard industries today and the impact, potential or real, of the variety of forms of partnership on safety and well-being at work. The contributors assess the effect of out-sourcing and of various forms of partnership and governance on safety at work and how they can be made to support the prevention of major accident hazards.